2009
DOI: 10.1002/jnr.22219
|View full text |Cite
|
Sign up to set email alerts
|

Microglia of rat ventral midbrain recovers its resting state over time in vitro: Let microglia rest before work

Abstract: Cortical or total brain cultures of microglia are commonly used as a model to study the inflammatory processes in Parkinson's disease. Here we characterize microglia cultures from rat ventral midbrain and evaluate their response to zymosan A. We used specific markers of microglia and evaluated the morphology, the phagocytic activity and reactive oxygen species (ROS) levels of the cells. During the first 10 days in vitro (DIV), cultures presented predominantly cells with a round morphology, expressing CD68 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(53 reference statements)
2
10
0
Order By: Relevance
“…The supernatant enriched with microglia was collected and centrifuged (200g, 5 min). Microglial cell culture purity was quantified after immunolabelling using CD11b antibody (1 : 200; Abcam, Belgium) and found to be above 90% (see details in the electronic supplementary material) in accordance with previous reports that used a similar isolation technique [18,28]. A total of 6 Â 10 4 viable cells ml 21 were seeded on P(TMC-CL) substrates secured at the bottom of a 24-well plate with a silicone o-ring (Epidor, Spain) and cultured in DMEM/F12 medium (Gibco) supplemented with 10% FBS and 1% P/S for 1 or 5 days.…”
supporting
confidence: 80%
“…The supernatant enriched with microglia was collected and centrifuged (200g, 5 min). Microglial cell culture purity was quantified after immunolabelling using CD11b antibody (1 : 200; Abcam, Belgium) and found to be above 90% (see details in the electronic supplementary material) in accordance with previous reports that used a similar isolation technique [18,28]. A total of 6 Â 10 4 viable cells ml 21 were seeded on P(TMC-CL) substrates secured at the bottom of a 24-well plate with a silicone o-ring (Epidor, Spain) and cultured in DMEM/F12 medium (Gibco) supplemented with 10% FBS and 1% P/S for 1 or 5 days.…”
supporting
confidence: 80%
“…The protocol here described originates microglial cultures that exceeds 97% purity and has been used as a model for activated CNS-resident microglia (Carson et al, 1998; Schmid et al, 2009) and to prepare polarized M1 and M2 phenotypes (Jang et al, 2013). Indeed, it was previously suggested that the isolation process is a sufficient stimulus to induce microglia activation (Cristóvão et al, 2010). There is a high controversy on whether neonatal microglia are less (Moussaud and Draheim, 2010) or more reactive than adult (Christensen et al, 2014) and aged cells (Njie et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these cells were analyzed either 24–48 h after isolation (Njie et al, 2012; Lai et al, 2013) or following trypsinization when kept in culture for several weeks in the presence of conditioned medium containing increased levels of mitogens (von Bernhardi et al, 2011). Such methods may promote microglia activation and bias the translation of culture findings, since it has been suggested that microglia may need some time in culture to recover its quiescent state (Cristóvão et al, 2010). Moreover, there are no means to isolate degenerating microglia for experimentation (Njie et al, 2012) once only the more resistant ones will survive to the isolation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively to microglia, in vitro cell models, either microglial cell lines, or primary microglia isolated from embryonic (Gingras et al, 2007 ) or neonatal animals (Floden and Combs, 2007 ), though largely used (Moussaud and Draheim, 2010 ), fail in mimicking adult behavior cells (Sierra et al, 2007 ). Furthermore, primary cultures of microglia were shown to change their activation profile according with the time in culture (Cristóvão et al, 2010 ). All of these features contribute to data inconsistency.…”
Section: Introductionmentioning
confidence: 99%